Evaluating the Effectiveness of Virtual Reality and Augmented Reality Technologies in the Training of Information Library Specialists - F, Umaraliyeva F.; D, Bayturayev T.; X, Maxmudov M.; N, Muminxodjayeva L.; I, Matmuradova M. (International Journal of Membrane Science and Technology, 2023)
In an era dominated by information technology, the role of information library specialists has become increasingly vital. These professionals are responsible for managing, organizing, and disseminating vast amounts of information. To keep pace with the evolving landscape of libraries and information services, the training of information library specialists has also undergone significant changes. One such transformation is the integration of virtual reality (VR) and augmented reality (AR) technologies into the training process. This article explores the efficacy of VR and AR technologies in enhancing the training of information library specialists, drawing insights from scientific studies and relevant literature.